Effect of the pH of the electrolyte on the formation and on the corrosion properties of ceria based coating on carbon steel. Issue 1 (26th July 2018) - Bourenane, Nadjette; Hamlaoui, Youcef; Remazeilles, Celine; Pedraza, Fernando
Abstract : The effects of the modification of the pH in 0.1 M cerium nitrate solutions in the elaboration and corrosion resistance of ceria based coatings on carbon steel are investigated. Increasing the concentration of acetic acid impedes an efficient electrodeposition. At low concentrations, acetic acid seems to prevent the precipitation of Ce(OH)3 and the formation of even films of cerium oxides is favored. The increase of pH through the addition of NaOH to the cerium nitrate solutions with 0.008 M of acetic acid is shown to provide superior corrosion resistance for exposures in air and immersed in 0.5 M NaCl for 30 days. Abstract : The effects of the modification of the pH in 0.1 M cerium nitrate solutions in the elaboration and corrosion resistance of ceria based coatings on carbon steel are investigated. Increasing the concentration of acetic acid impedes an efficient electrodeposition. The increase of pH through the addition of NaOH to the cerium nitrate solutions with 0.008 M of acetic acid is shown to provide superior corrosion resistance.